2019
DOI: 10.1002/jcla.23086
|View full text |Cite
|
Sign up to set email alerts
|

Circ‐MTO1 correlates with favorable prognosis and inhibits cell proliferation, invasion as well as miR‐17‐5p expression in prostate cancer

Abstract: Background This study aimed to investigate circular RNA‐mitochondrial tRNA translation optimization 1 (circ‐MTO1) expression in tumor tissue and its correlation with clinical characteristics and survival profiles, as well as its effect on cancer cell functions in prostate cancer. Methods A total of 298 primary prostate cancer patients were included. Reverse transcription‐quantitative polymerase chain reaction was conducted to evaluate circ‐MTO1 expression in tumor tissue and paired adjacent tissue. Disease‐fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 24 publications
(50 reference statements)
4
37
0
Order By: Relevance
“…Previous prognostic studies on both serum and tissue from PCa patients support our results. However, these studies were all based on RT-PCR 17 , 21 23 . Hoey et al .…”
Section: Discussionmentioning
confidence: 99%
“…Previous prognostic studies on both serum and tissue from PCa patients support our results. However, these studies were all based on RT-PCR 17 , 21 23 . Hoey et al .…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of cir-ITCH inhibited the growth, migration, and invasion of PCa cells, proving its tumor inhibitory function in PCa. Both tumor-promoting as well as tumor-suppressing roles in PCa have been reported for miR-17 [28,32]. Evidence has shown that high or low miR-17 expression in the blood is related to the progression of PCa [33].…”
Section: Discussionmentioning
confidence: 99%
“…The higher expression of circ-MTO1 in tumor tissue compared to normal tissues suggests a better prognosis. Overexpression of circ-MTO1 in prostate cancer cells can inhibit cell viability and the expression of miR-17 [ 28 ]. circRNA circfoxo3 reportedly promotes the development of prostate cancer by sponging miR-29a-3p [ 29 ], while circSMARC5 is upregulated in prostate cancer and its expression is androgen-responsive [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The circRNAs identified in this study have not been reported previously. Therefore, we performed a literature review of circRNAs in PCa in the PubMed database, identifying 13 studies ( Xia et al, 2018 ; Shen et al, 2019 ; Song et al, 2019 ; Wang et al, 2019 ; Wu et al, 2019 ; Hu and Guo, 2020 ; Kong et al, 2020 ; Li T. et al, 2020 ; Ou et al, 2020 ; Shan et al, 2020 ; Yan et al, 2020 ; Zheng et al, 2020a , b ) of 18 circRNA–miRNA interactions. The miRNAs identified in this study have previously been shown to play important roles in PCa.…”
Section: Discussionmentioning
confidence: 99%